2020
DOI: 10.1093/forestry/cpaa026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance distribution of SSR markers and economically important quantitative traits in a progeny trial ofProsopis chilensis(Leguminosae): implications for the ‘Algarrobo’ management programme

Abstract: Prosopis chilensis (Molina) Stuntz (Leguminosae) is a valuable native species in Argentina included in the Prosopis Management Programme. Natural provenances show important height and shape differentiation throughout their distribution in the Monte Desert. The availability of progeny trials provides an opportunity to quantify genetic differentiation among provenances and test the relative importance of demographic vs adaptive processes on morphological variation. We quantified both genetic and quantitative dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…When variation distribution is analyzed at lower hierarchical levels, most of the variation (79.3%) was found at the lowest level (individuals), which is expected in outcrossing species as Prosopis (Bessega et al., 2019; Chequer Charan et al., 2020; Roser et al., 2017). However, the AMOVA indicated that the genetic variation between populations within basins was low and significant (7.47%) and almost the same as the percentage obtained considering the between‐basin component (7.4%).…”
Section: Discussionmentioning
confidence: 98%
“…When variation distribution is analyzed at lower hierarchical levels, most of the variation (79.3%) was found at the lowest level (individuals), which is expected in outcrossing species as Prosopis (Bessega et al., 2019; Chequer Charan et al., 2020; Roser et al., 2017). However, the AMOVA indicated that the genetic variation between populations within basins was low and significant (7.47%) and almost the same as the percentage obtained considering the between‐basin component (7.4%).…”
Section: Discussionmentioning
confidence: 98%